Tantangan Bagi Penyandang Disabilitas Penglihatan dalam Mengakses Pekerjaan - Yani Fathur Rohman (Indonesian Center for Religion and Society Studies (InTReSt), 2019)
Studies of disability,including people with visual impairments has shifted towards the interaction of individuals with obstacles in the environment. This systematic review of the literatures aims to increase the understanding of social exclusion as a multi dimensional aspect. Based on the substantive mapping, various collected literature can be grouped into cultural exclusion and structural exclusion includes; 1) stigma as a paradox explores theimpact of stigma for people with visual impairment related to work; 2) career mobility, job satisfaction, and social exclusion discuss the lack of job satisfaction and career promotion forpeople with visual impairments; 3) the limitation of work accommodations explain abou tphysical environment constraints; and 4) education and skill as as tructural problem discususs about the relationship between individual and minimal services from state. This study found that social exclusion at the structural level is the impact of the existence of social exclusion at the cultural level, which is then perpetuated by structure through various policies both government and workplaces.